Bad Luck for the Anti‐Luck Epistemologist. Issue 4 (1st December 2016) - Borges, Rodrigo
Abstract: Anti‐luck epistemologists tell us that knowledge is incompatible with epistemic luck and that epistemic luck is just a special case of luck in general. Much work has been done on the intricacies of the first claim. In this paper, I scrutinize the second claim. I argue that it does not survive scrutiny. I then offer an analysis of luck that explains the relevant data and avoids the problems from which the current views of luck suffer. However, this analysis of luck is of no help to the anti‐luck epistemologist for it uses knowledge to explain luck, making this account of knowledge circular. The main lesson is that the only viable analysis of luck is not suited for the anti‐luck epistemologist's coveted noncircular analysis of knowledge.